Normothermic donor heart perfusion: current clinical experience and the future. (7th July 2014) - Messer, Simon; Ardehali, Abbas; Tsui, Steven
Abstract Following the first successful heart transplant in 1967, more than 100 000 heart transplants have been carried out worldwide. These procedures have mostly relied on cold ischaemic preservation of the donor heart because this simple technique is inexpensive and relatively reliable. However, the well‐known limitations of cold ischaemic preservation imposes significant logistical challenges to heart transplantation which put a ceiling on the immediate success on this life‐saving therapy, and limits the number of donor hearts that can be safely transplanted annually. Although the theoretical advantages of normothermic donor heart perfusion have been recognised for over a century, the technology to transport donor hearts in this state has only been developed within the last decade. The Organ Care System (OCS) which is designed and manufactured by TransMedics Inc. is currently the only commercially available device with this capability. This article reviews the history of normothermic heart perfusion and the clinical experience with the TransMedics OCS to date. We have also attempted to speculate on the future possibilities of this innovative and exciting technology.